Staged privatization: transforming state-owned enterprises into market-based firms - Jiang, Kun; Wang, Susheng (Mohr Siebeck, 2016)
Most privatizations around the world, especially in developed economies, are staged processes involving multiple stages of share lockup and unlocking in the stock market. This paper proposes a theory on staged or step-by-step privatization. We show that such an approach is efficient, in the sense that it can successfully transform state-owned enterprises into efficient market-based firms. Our theory explains the popularity of staged privatizations around the world. We have also conducted empirical analysis, yielding supporting evidence for our theory.